Characterization of the Adaptive Amoxicillin Resistance of Lactobacillus casei Zhang by Proteomic Analysis - Wang, Jicheng; Guo, Huiling; Cao, Chenxia; Zhao, Wei; Kwok, Lai-Yu; Zhang, Heping; Zhang, Wenyi (Frontiers in Microbiology, 2018)
Amoxicillin is one of the most commonly prescribed antibiotics for bacterial infections and gastrointestinal disorders. To investigate the adaptation of Lactobacillus (L.) casei Zhang to amoxicillin stress, an iTRAQ-based comparative proteomic analysis was performed to compare the protein profiles between the parental L. casei Zhang and its amoxicillin-resistant descendent strains. Our results revealed a significant increase in the relative expression of 38 proteins (>2.0 folds, P<0.05), while the relative expression of 34 proteins significantly decreased (<-2.0 folds, P<0.05). The amoxicillin-resistant descendent strain exhibited marked alterations in carbohydrate and amino acid metabolism. Moreover, certain components involving in membrane metabolism were activated. The differences in the proteomic profiles between the two strains might explain the enhanced stress resistance of the adapted bacteria.